Fully Human Immunoglobulin G From Transchromosomic Bovines Treats Nonhuman Primates Infected With Ebola Virus Makona Isolate. (16th July 2018) - Luke, Thomas; Bennett, Richard S; Gerhardt, Dawn M; Burdette, Tracey; Postnikova, Elena; Mazur, Steven; Honko, Anna N; Oberlander, Nicholas; Byrum, Russell; Ragland, Dan; St. Claire, Marisa; Janosko, Krisztina B; et al.
Abstract: Transchromosomic bovines (Tc-bovines) adaptively produce fully human polyclonal immunoglobulin (Ig)G antibodies after exposure to immunogenic antigen(s). The National Interagency Confederation for Biological Research and collaborators rapidly produced and then evaluated anti-Ebola virus IgG immunoglobulins (collectively termed SAB-139) purified from Tc-bovine plasma after sequential hyperimmunization with an Ebola virus Makona isolate glycoprotein nanoparticle vaccine. SAB-139 was characterized by several in vitro production, research, and clinical level assays using wild-type Makona-C05 or recombinant virus/antigens from different Ebola virus variants. SAB-139 potently activates natural killer cells, monocytes, and peripheral blood mononuclear cells and has high-binding avidity demonstrated by surface plasmon resonance. SAB-139 has similar concentrations of galactose-α-1, 3-galactose carbohydrates compared with human-derived intravenous Ig, and the IgG1 subclass antibody is predominant. All rhesus macaques infected with Ebola virus/H.sapiens-tc/GIN/2014/Makona-C05 and treated with sufficient SAB-139 at 1 day (n = 6) or 3 days (n = 6) postinfection survived versus 0% of controls. This study demonstrates that Tc-bovines can produce pathogen-specific human Ig to prevent and/or treat patients when an emerging infectious disease either threatens to or becomes an epidemic.